The ULF wave foreshock boundary: Cluster observations. Issue 6 (1st June 2015) - Andrés, Nahuel; Meziane, Karim; Mazelle, Christian; Bertucci, Cesar; Gómez, Daniel
Abstract The interaction of backstreaming ions with the incoming solar wind in the upstream region of the bow shock gives rise to a number of plasma instabilities from which ultralow frequency (ULF) waves can grow. Because of their finite growth rate, the ULF waves are spatially localized in the foreshock region. Previous studies have reported observational evidence of the existence of a ULF wave foreshock boundary, whose geometrical characteristics are very sensitive to the interplanetary magnetic field (IMF) cone angle. The statistical properties of the ULF wave foreshock boundary (UWFB) are examined in detail using Cluster data. A new identification of the UWFB is presented using a specific and accurate criterion for identification of boundary crossings. This criterion is based on the degree of IMF rotation as Cluster crosses the boundary. The obtained UWFB is compared with previous results reported in the literature as well as with theoretical predictions. Also, we examined the possible connection between the foreshock boundary properties and the ion emission mechanisms at the bow shock.